PARTISIPASI UMAT DALAM MENGIKUTI PENDALAMAN KITAB SUCI DI PAROKI SANTO PETRUS DAN PAULUS AMPAH - Pritiani Pritiani; Silvester Adinuhgra; Romanus Romas; Titi Christiana (Sepakat : Jurnal Pastoral Kateketik, 2021)
This study aims to find out how the people’s participation in following the deepening of Scriptures in the Parish of Saints Peter and Paul Ampah. This research is based on the phenomenon that occurs in the field that the deepening activities of Scripture are still less desirable to the people. The involvement of people in participating in the deepening activities of Scripture in Santo Petrus and Paulus Ampah Parish is still lacking, both before the Covid-19 pandemic and during the current Covid-19 pandemic. The type of research used in this research is descriptive qualitative research. This research was conducted on May at the parish of Saints Peter and Paul Ampah in particular in four neighborhoods: the neighborhood of Saint Sicily, the neighborhood of Santa Maria, the neighborhood of Saint Joseph and the neighborhood of Saint Francis. The informants are 14 people consisting of 1 Parish Priest, 3 Catechists, 4 environmental chairmen and 6 parishioners. Data Collection techniques through observation, interviews and documentation. The data analysis techniques used is the model of Miles and Huberman wich consist of three stages, data reduction, data presentation and conclusion drawing.